Factors Influencing Stunting among Children in Pekanbaru City - Sari, Lapeti; ., Mardiana; ., Syapsan; Mayes, Anthoni; Ningsih, Rahmita Budiarti; Putri , Datia Dwi (Journal of Ecohumanism, 2025)
Stunting is a chronic condition caused by prolonged nutritional deficiencies, leading to impaired growth and development in children. This study examines the factors influencing stunting among children in Pekanbaru City, focusing on maternal age, age at first marriage, family income, maternal education level, and birth weight. A quantitative descriptive approach was employed, analyzing data from 77 respondents using multiple linear regression. The findings reveal that maternal education is the most significant factor affecting stunting. The results underscore the importance of maternal education in reducing stunting prevalence. This research contributes valuable insights for policymaking to address stunting issues.